Pemanfaatan Aplikasi Digital dalam Operasional Kedai Sembako Indah Untuk Perluasan Pasar dan Peningkatan Pelayanan - Sari, Indah (Journal of Informatics Management and Information Technology, 2025)
Digital transformation is one of the key factors in increasing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the industrial era 4.0. Kedai Sembako Indah, as one of the MSMEs in the staple food trading sector, faces challenges in operational efficiency, financial recording, and marketing. This study aims to analyze the use of digital applications in supporting the daily operational activities of Kedai Sembako Indah, including stock management, sales transactions, and marketing strategies. The method used is a descriptive qualitative study with a case study approach. Data were collected through interviews, direct observation, and documentation during the implementation process of digital applications such as cashier applications (point of sale), e-wallet platforms, and social media. The results of the study show that the use of digital applications has a positive impact on time efficiency, accuracy of transaction recording, and increased interaction with customers. In addition, the use of social media also helps expand market reach. The main obstacles faced are limited digital literacy and initial adaptation to new technologies. In conclusion, operational digitalization through simple applications can be a strategic initial step in strengthening the performance and sustainability of MSMEs such as Kedai Sembako Indah. Continuous assistance is needed so that technology adoption can run optimally.